(untitled) (Education in the 21st Century, 2023)
In an article titled ,” Combined lesson, features of the lesson application"we tried to show the features of the combined lesson application, due to the nature of the taught material and the originality of the writer’s imaginative system, the age groups of students. We have considered several approaches to the application of the combined lesson in accordance with the fundamental features of the combined lesson. The purpose of the article: with the help of interesting observations to reveal the essence of the above type of lesson, the principles of teaching the material in this format, indicating and justifying the advantages due to the relevant features of this method of teaching, the features arising from the purpose of training. The novelty of the study: consideration of various approaches to the application of the agreed class, their features. The above-mentioned teaching method investigated effective means of transition from the material studied to the material, in combination with literature and other subjects, the philosophical and psychological layers of the literary image were emphasized. The relevance of the research determines the consideration of the process of teaching literary works by the requirements of modern teaching methodology, making it consonant with modern educational programs. In the article we have shown the effectiveness of using a combined lesson with different approaches, the possibility of a more meaningful and multi-layered study of a work of art with their help. As a result of the research, we came to the following conclusions: a combined lesson contributes to a deeper analysis of the taught material, the formation of students’ skills in constructing comparative and analytical speech, the development of imaginative thinking, a broad representation of a work of art, makes the lesson more interesting and meaningful.